PEMANFAATAN BENANG DARISERAT NENAS SEBAGAI DAWAI PENGUAT PADA KARET V-BELT - Luftinor Luftinor (Balai Riset dan Standardisasi Industri Palembang, 2010)
This research aims to improve the efficiency of pineapple fiber are not yet widey used, especially in textile and rubber industry and pineapple plant until now regarded as wate and are generally discarded or burned. The extent to which yarn from pineapple fibers can be used as reinforcement inrubber fine wires V-belt has conducted reaserch by varying the amount of carbon black fillers each 15 Phr,30 Phr, 45 Phr and 60 Phr of the compound process and varying the ratioof the number of fine wires amplifiers pineapple yarn and fine wires of nylon yarn reinforment of their respective 25%, 50%, 75 and 100% n the printing process of the rubber V-belt. Rubber V-belt is obtained from the result of experiments carried out tensile strength test and modulus test. These data indicate that the test result of yarn from pinapple fibers can be used as reinforment in rubber fine wires V-belt and meet the standard SNI 06-1546-1989 with a maximu value of 240 kg/cm² of modulus and a minimum tensile strength of 400kg/cm². the best result obtained in experiments using 50% fine wires of yarn peniappleand carbon black fibers with 45 Phr tensile strength value 421kg/cm².